Discordance for Cornelia de Lange syndrome in twins. Issue 5 (October 1976) - Stevenson, R E; Scott, C I
Abstract : A male infant, the first-born of twins, with features of Cornealia de Lange syndrome is described. His normal twin was discordnat for 3 of the 14 blood loci tested. Chromosomes from the affected infant appeared normal. Though the aetiological basis for the Cornealia de Lange syndrome remains obscure, most authorities accept genetic rather than environmental causation. The present findings of discordance for Cornelia de Lange syndrome in twins support this view but do not clarify the mode of inheritance.